KARAKTERISTIK RUMAH TANGGA MISKIN PERKOTAAN DAN PERDESAAN DI PROVINSI GORONTALO - Sulkifar Sulkifar; Sri Endang M. saleh; Sri Indriyani S. Dai (Politeknik Negeri Ambon, 2026)
Introduction: Poverty remains a major development issue in Gorontalo Province, particularly due to disparities between urban and rural areas. Differences in socio-economic structures shape the characteristics of poor households, leading to varying patterns of poverty across regions. Understanding these differences is essential to formulating more effective, targeted poverty-alleviation policies. This study aims to analyze and compare the characteristics of poor households in urban and rural areas of Gorontalo Province, focusing on education level, employment status, household size, and the age of the household head.Methods: This study employed a quantitative, descriptive, and comparative approach. The data were derived from the 2024 National Socio-Economic Survey (Susenas) microdata published by the Central Bureau of Statistics (BPS). The sample consisted of 265 poor households in Gorontalo Province. Data analysis was conducted using cross-tabulation and Chi-Square tests at a 5 percent significance level to examine differences in household characteristics between urban and rural areas.Results: There are no statistically significant differences in education level, number of household members, and age of household heads between urban and rural poor households (p-values> 0.05). However, a significant difference is found in employment status (p-value < 0.05). Rural poor households are predominantly employed as permanent and non-permanent laborers, whereas urban poor households are more likely to be self-employed or salaried workers. These results suggest that employment structure is the primary distinguishing factor between urban and rural poverty characteristics.Conclusion and suggestion: The study concludes that poverty characteristics in Gorontalo Province are multidimensional, with employment status being the key differentiating variable between urban and rural poor households. Therefore, poverty alleviation policies should be region-specific, emphasizing employment quality improvement, income stability, and human resource development in accordance with local economic conditions. Keywords: Poor Households, Poverty, Rural, Urban